微小残留病在成人急性髓系白血病非预后良好型患者中的预后价值 (Zhonghua Xue Ye Xue Za Zhi, 2017)
OBJECTIVE: To explore impact of minimal residual leukemia (MRD) on outcomes in the non-favorable risk adults with de novo acute myeloid leukemia (AML). METHODS: From January 2008 to February 2016, data of consecutive newly-diagnosed non-favorable risk adults with AML (non-APL) according to SWOG criteria who achieved morphologic leukemia-free state (MLFS) and received continuous chemotherapy were assessed retrospectively. RESULTS: 292 AML patients were enrolled, 150 (51.4%) were male. Median age was 46 years (range, 18–65 years). Using the SWOG cytogenetic classification, 186 (63.7%), 49 (16.8%) and 57 (19.5%) patients belonged to intermediate, unfavorable and unknown categories, respectively. With a median follow-up period of 15 months (range, 1 to 94 months) in survivors, the probabilities of cumulative rates of relapse (CIR), disease free survival (DFS) and overall survival (OS) at 2-years were 51.6%, 42.6% and 60.0%, respectively. Multivariate analyses showed that MRD positive (defined as Q-PCR WT1 mRNA ≥0.6% or any level of abnormal blast population detected by flow cytometry) after achieving MLFS and PLT<100×10(9)/L were common adverse factors affecting CIR and DFS. In addition, positive FLT3-ITD mutation and CRp/CRi had negatively impact on CIR, DFS and OS. Monosomal karyotype was adverse factors affecting CIR and OS. Age ≥44 years and unfavorable-risk of SWOG criteria were associated with shorter DFS. CONCLUSION: MRD level after achieving MLFS had prognostic significance on outcomes in non-favorable adults with AML who received continuous chemotherapy after achieving MLFS.